Extracorporeal cardiopulmonary resuscitation for refractory out‐of‐hospital cardiac arrest: Lessons learned from recent clinical trials - Stephanie DeMasi; Megan Donohue; Lisa Merck; Jarrod Mosier; for the Strategies to Innovate Emergency Care Clinical Trials Network (SIREN) investigators (Journal of the American College of Emergency Physicians Open)
Abstract Cardiac arrest is a leading contributor to morbidity and mortality in the United States. Survival has been historically dependent on high‐quality cardiopulmonary resuscitation (CPR) and rapid defibrillation. However, a large percentage of patients remain in refractory cardiac arrest despite adherence to structured advanced cardiac life support algorithms in which these factors are emphasized. Veno‐arterial extracorporeal membrane oxygenation is becoming an increasingly used rescue therapy for patients in refractory cardiac arrest to restore oxygen delivery by extracorporeal CPR (ECPR). Recently published clinical trials have provided new insights into ECPR for patients who sustain an outside hospital cardiac arrest (OHCA). In this narrative review, we summarize the rationale for, results of, and remaining questions from these recently published clinical trials. The existing observational data combined with the latest clinical trials suggest ECPR improves mortality in patients in refractory arrest. However, a mixed methods trial is essential to understand the complexity, context, and effectiveness of implementing an ECPR program.